Evaluation of the experience and attitude of the population to the salt and salty foods, on the way to prevent cardiovascular diseases. (On the example of Almaty) - Arailym Beisbekova; Feruza Ospanova; Toregeldi Sharmanov (Ķazaķstannyṇ Klinikalyķ Medicinasy, 2017)
The purpose: of this work was to fnd out the attitude and habits of consumption of salt and salty food in the city of Almaty and about the methods of CVD prevention. Methods: To achieve this goal was used a social-method, using a questionnaire consisting of 5 blocks and 31 questions. We evaluated the results of a questionnaire survey of 340 respondents, including 174 women and 166 men aged 25-64 years. Total formed four strata - men aged 25-44, women aged 25-44, men 45-64 years and women 45-64. Results: Among all respondents, 9.4% answered that they often dosed the food and more than 60% of the respondents believed that they consume salt in the right amount, but at the same time 14.1% answered that they don’t know about the harmful use of large amounts of salt and 8,8% believe that there is no harm from this. Conclusion: Communication works with the population about the harmful use of salt and its consequences is not fully implemented. Therefore, it is necessary to strengthen communication work to inform the public about excessive consumption of salt and salty foods.